IMPACT OF SUBLETHAL CONCENTRATION OF ENDOSULFAN ON BIOCHEMICALS AND HISTOLOGY OF ORGAN TISSUES OF FRESHWATER FISH, LABEO ROHITA (HAMILTON, 1822) - W. P. S. INDIRABAI; THARANI, G. GEETHA; P. SEETHA (The Bioscan, 2010)
Exposure of the freshwater fish, Labeo rohita to sublethal concentration (0.05 ppm) of endosulfan over a period of 96 (hrs.) has revealed that the organochlorine pesticide had a profound effect on the total content of carbohydrates, lipids and proteins in the muscle tissue (mg%) and proteins in the liver tissues. Histological observations of the experimental liver, kidney and gills have shown pathological lesions leading to necrosis of hepatocytes, glomorulus of kidney and primary and secondary gill filaments of gills, which was on par with the duration of exposure of fish to endosulfan and thereby affect homeostasis of fish, L. rohita.